The Arabidopsis GolS1 promotor as a potential biosensor for heat stress and fungal infection? - Janse van Rensburg, Henry Christopher (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.